2018
DOI: 10.1111/pce.13145
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 mediates nitrate‐induced iron chlorosis by regulating iron homeostasis in rice

Abstract: The uptake of nitrate by plant roots causes a pH increment in rhizosphere and leads to iron (Fe) deficiency in rice. However, little is known about the mechanism how the nitrate uptake-induced high rhizosphere pH causes Fe deficiency. Here, we found that rice showed severe leaf chlorosis and large amounts of Fe plaque were aggregated on the root surface and intercellular space outside the exodermis in a form of ferrihydrite under alkaline conditions. In this case, there was significantly decreased Fe concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…However, Mn uptake drastically increased in the transgenic lines in 0.5 mM NO 3 - ( Supplementary Figure S5 and Figure 4D ). It was recently shown that NO 3 - uptake induces external alkalization, reducing Fe/Mn concentrations by enhancing the levels of H 2 O 2 in rice ( Chen et al, 2018 ). In this study, we performed hydroponic experiments in MES buffered nutrient medium (to control pH) and nutrient treatments were replaced every 2 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, Mn uptake drastically increased in the transgenic lines in 0.5 mM NO 3 - ( Supplementary Figure S5 and Figure 4D ). It was recently shown that NO 3 - uptake induces external alkalization, reducing Fe/Mn concentrations by enhancing the levels of H 2 O 2 in rice ( Chen et al, 2018 ). In this study, we performed hydroponic experiments in MES buffered nutrient medium (to control pH) and nutrient treatments were replaced every 2 days.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate root uptake increases pH in the rice rhizosphere, which triggers Fe deficiency. This is due to an increase in H 2 O 2 induced by RBOH1, with a concomitant boost in lignin biosynthesis and low phenolic secretion, which blocks apoplastic Fe mobilization efficiency [161].…”
Section: Regulation Of Iron-responsive Element-iron Regulatory Proteimentioning
confidence: 99%
“…For example, SPAD value decreased or increased after a change in petiole nitrate concentration. Chen et al [17] found that when nitrate-N was the only N source, the increase of rhizosphere pH led to the slow growth and yellowing of new leaves, which was mainly attributed to an increase of phenolic compounds in the phenylpropane metabolism pathway in roots under high pH conditions. Meanwhile, Schijlen et al [18] also found that more rutin and other flavonoid polyphenols appeared when Arabidopsis thaliana seedlings grew for two days under N deficiency conditions.…”
Section: Introductionmentioning
confidence: 99%